150k views
4 votes
Which polynomial represents the difference below? 7x8 + 8x6 - 2x + 9 - (4x8 + 3x7 + 3)

User Ulf Aslak
by
5.3k points

2 Answers

2 votes

Consider the difference of polynomials
(7x^8 + 8x^6 - 2x + 9) - (4x^8 + 3x^7 + 3).

The first thing you have to do is take that "minus" sign through the parentheses containing the second polynomial (just change sign + to - and sign - to +):


(7x^8 + 8x^6 - 2x + 9) - (4x^8 + 3x^7 + 3)=7x^8+8x^6-2x+9-4x^8-3x^7-3.

Then combine terms with the same degree:


7x^8+8x^6-2x+9-4x^8-3x^7-3=(7x^8-4x^8)-3x^7+8x^6-2x+(9-3).

Note that


7x^8-4x^8=(7-4)x^8=3x^8,\\ \\9-3=6.

Thus,


(7x^8 + 8x^6 - 2x + 9) - (4x^8 + 3x^7 + 3)=3x^8-3x^7+8x^6-2x+6.

User LeonardChallis
by
5.3k points
5 votes
Use associativity and distributivity properties:

7x^8 + 8x^6 - 2x + 9 - (4x^8 + 3x^7 + 3)=(7-4)x^8-3x^7+8x^6-2x\\+(9-3)\\=3x^8-3x^7+8x^6-2x+6
We are done.